2018
DOI: 10.21037/jtd.2018.03.66
|View full text |Cite
|
Sign up to set email alerts
|

HIV-negative pulmonary disease caused by nontuberculous mycobacteria in Southern Brazil: clinical and microbiological characterization

Abstract: Background: Nontuberculous mycobacteria (NTM) have been identified with increasing frequency in the clinical practice. The aim of this study was to characterize NTM isolates in respiratory specimens from patients with pulmonary disease and to correlate this with clinical/radiological findings, decision to start treatment and outcomes. Methods: A cross-sectional descriptive study was performed and included all patients who had at least one NTM isolated in respiratory specimens between 2011 and 2014. NTM culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In addition, species implicated in pulmonary disease were also identified: M. avium and M. abscessus 6 , 18 . With regard to the potentially pathogenic NTM species, the findings of this study are similar to that of clinical practice and other studies carried out worldwide, with the most common species being M. avium , M. intracellulare , M. kansasii , M. chelonae , M. abscessus , M. fortuitum , and M. peregrinum 19 - 21 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, species implicated in pulmonary disease were also identified: M. avium and M. abscessus 6 , 18 . With regard to the potentially pathogenic NTM species, the findings of this study are similar to that of clinical practice and other studies carried out worldwide, with the most common species being M. avium , M. intracellulare , M. kansasii , M. chelonae , M. abscessus , M. fortuitum , and M. peregrinum 19 - 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Another important aspect with respect to the frequency of NTM in patients with HIV in this study was the fact that 16% of the NTMs isolated in these patients were identified as Mycobacterium sp, which highlights the need to validate the rapid laboratory methods, preferably molecular methods, which can identify NTM 8 , 19 .…”
Section: Discussionmentioning
confidence: 90%
“…Recently, studies have been frequent in non-HIV-infected patients with Mycobacterium intracellulare (59.1%) and M. avium (14.3%) species as the most isolated. (28) It is important to highlight that, among the potentially pathogenic species, those belonging to the M. avium and M. kansasii complex (slow-growing mycobacteria) are the most commonly isolated, and both cause mainly pulmonary infection, the former being frequently responsible for disseminated disease and death in HIV-positive patients. (18,23,29) By analyzing only patients with confirmed cases of NTMPD, our results showed that, if we evaluate the data independently of HIV serology, M. kansasii still remains the most commonly isolated species (37.5%), followed by MAC (20.8%) and M. fortuitum (12.5%).…”
Section: ❚ Discussionmentioning
confidence: 99%
“…In Brazil, a country with high endemicity for TB (20 th position according to WHO classification), the prevalence and incidence of NTM infections are not well known since the disease does not require compulsory notification for the health system. The isolation of NTM species in Brazil differs according to the region; however, it is possible to observe a predominance of Mycobacterium avium complex (MAC), such as M. avium , and M. intracellulare , M. kansasii , and M. fortuitum , causing active NTM disease 1 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%